2015
DOI: 10.1149/2.0391509jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Liquid Metal Anode SOFCs

Abstract: Liquid metal anode (LMA) solid oxide fuel cells (SOFCs) are a promising type of high temperature fuel cell suitable for the direct oxidation of gaseous or solid fuel. Depending upon the operating conditions they can be run in four different modes. In this first of a series of studies concerning the mechanism of reaction and species transport in LMA SOFCs, the oxidation of hydrogen fuel in a liquid tin anode has been investigated. An electrochemical model is developed based upon fast dissolution of hydrogen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…But due to the sluggish nature of oxygen transport (5.3×10 -5 cm -2 s -1 @ 800 o C) in liquid Sn (16), the current limit set by mass transport of oxygen is inevitably low, resulting in a less satisfactory power density of fuel cell. Toleuova et al (17,18) introduced H 2 into the LTA to help remove oxygen content, and the H 2 fueled electrochemical system is operated at a potential between OCPs of H 2 and Sn. This high operation voltage makes SnO 2 formation thermodynamically unfavorable, but the limited over potential (<0.1 V) also left the power density inherently low.…”
Section: Introductionmentioning
confidence: 99%
“…But due to the sluggish nature of oxygen transport (5.3×10 -5 cm -2 s -1 @ 800 o C) in liquid Sn (16), the current limit set by mass transport of oxygen is inevitably low, resulting in a less satisfactory power density of fuel cell. Toleuova et al (17,18) introduced H 2 into the LTA to help remove oxygen content, and the H 2 fueled electrochemical system is operated at a potential between OCPs of H 2 and Sn. This high operation voltage makes SnO 2 formation thermodynamically unfavorable, but the limited over potential (<0.1 V) also left the power density inherently low.…”
Section: Introductionmentioning
confidence: 99%
“…The previous paper (Part I) described the fundamental electrochemistry of such a LMA SOFC system. 3 It was demonstrated that the oxidation of hydrogen takes place via a Chemical-Electrochemical mechanism, (so-called CE mode), whereby hydrogen undergoes fast dissolution, then rate-determining homogeneous oxidation by oxygen dissolved in the liquid tin, followed by diffusion-controlled anodic oxygen injection to replace oxygen removed by the chemical reaction. In summary, the process involves:…”
Section: Introductionmentioning
confidence: 99%
“…potentiostatic and open-circuit), whereby electrode potential is switched between a fixed value E and open-circuit. During the open-circuit periods, hydrogenreacts with oxygen dissolved in tin according to a Chemical-Electrochemical (CE) mechanism3 . In the first regime (Regime 1) the flow of H2 into the tin is constant, whereas in the second (Regime 2) it is intermittent.…”
mentioning
confidence: 99%
“…In molten carbonate media, the controlling anode reactions potentially include the complete oxidation of carbon [1] and/or the chemical gasification of carbon (reverse Boudouard reaction, [2]) followed by the oxidation of CO [3]. Carbonate ions are regenerated through reaction with oxygen anions [4], generated at the cathode [5] (6).…”
Section: Introductionmentioning
confidence: 99%